Blockchain applicability: brilliant earth diamonds - Frossard Silva-Rêgo, Bernardo; Moura, Stephanie T.G (Henry Stewart Talks, 2023)
This case study illustrates the potential and applicability of blockchain in transforming how different businesses operate. The example of Brilliant Earth demonstrates the use of blockchain in the supply chain to provide transparency and accountability.